(untitled) (Tanzania Medical Journal, 2025)
Background Low back pain and radiculopathy are major global health concerns, with lumbar disc degeneration increasingly prevalent among young adults. However, data on its occurrence in this demographic region is limited, underscoring the need for targeted research. Objective To assess the magnitude of spine degenerative disease and identify related risk factors among young adults undergoing lumbar spine MRI at Muhimbili Orthopedic Institute (MOI). MethodsA hospital-based cross-sectional study was conducted at MOI) from November 2022 to April 2023, enrolling young adults experiencing lower back pain with or without radiculopathy who were referred for lumbar spine MRI. Comprehensive data collection included socio-demographic information, risk factors, and clinical symptoms through structured questionnaires. MRI findings were documented using a specially designed data collection tool. Statistical analysis was performed using SPSS version 23, with Chi-square and Fisher's exact tests used to examine associations between variables. Results This study involved 88 patients between the ages of 20 and 39 years (mean age 32.34), with females comprising 54.5% of the study participants. Lumbar spine degenerative disease was identified in 92% of participants. The most prevalent symptom was lower back pain accompanied by radiculopathy (73%), while disc bulge was the most common MRI finding (89.8%). There was a significant association between lower back pain with radiculopathy and lumbar nerve root compression (P<0.05), as well as between high BMI and the presence of lumbar spine degenerative disease (P<0.05). Conclusion Ninety-two percent of young adults referred for lumbar spine MRI at MOI had lumbar spine degenerative disease. The most common symptom was lower back pain with radiculopathy, and the most frequent MRI finding was a disc bulge. The presence of nerve root compression on MRI correlated with lower back pain with radiculopathy, and a high BMI was significantly linked to lumbar spine degenerative disease. Recommendation Further studies are needed to explore the progression of degenerative changes over time, as well as preventive strategies and early interventions aimed at high-risk groups, to reduce the burden of lumbar spine degeneration in younger populations.